Analisis Ketimpangan Distribusi Pendapatan Kabupaten/Kota di Provinsi Bali - Mega Arafah; Rifki Khoirudin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2022)
Inequality of income distribution is a condition of different levels of economic prosperity which is reflected in differences in income levels so that there are rich and poor people. Development is carried out in a sustainable manner with the aim of achieving a prosperous society by utilizing the available resources and potential to the fullest. However, the results of development still lead to income inequality. This study aims to determine the effect of poverty, education, HDI, economic growth, and population on the inequality of income distribution in districts/cities in Bali Province in 2011-2021. The analytical method used is the panel data regression model. The results of this study indicate that the level of poverty affects the inequality of income distribution, while education, HDI, economic growth and population have no effect on the inequality of income distribution.